Gut-wrenching : a phenomenological investigation of somatic responses to disgust in American Horror Story : Freak Show - Lauwrens, Jennifer (University of Pretoria, 2024)
Dissertation (MA (Visual Culture Studies))--University of Pretoria, 2024.